Application of waste oil in asphalt rejuvenation and modification: A comprehensive review. (18th July 2022) - Yan, Shiao; Dong, Qiao; Chen, Xueqin; Zhou, Changjun; Dong, Shi; Gu, Xingyu
Highlights: Waste oil includes cooking oil, engine oil, and biomass categories. Waste oil can be used for asphalt rejuvenation and modification. The composite rejuvenation/modification of WO and other materials can make asphalt have more comprehensive properties. The properties of recycled/modified asphalt mixtures need to be monitored after long-term aging. Abstract: Waste oil (WO) is an important recyclable resource that can be used for asphalt rejuvenation and modification applications. This paper summarizes the current research on WO application in rejuvenating aged asphalt and modifying asphalt. First, the basic and chemical properties of WO and the preparation process of rejuvenated asphalt and modified asphalt were introduced. Then the various properties including basic physical, rheological, fatigue, adhesion, chemical, and mixture properties were summarized separately. Finally, the aging resistance and economic and environmental benefits were presented. The review work shows that WO may restore the properties of aged asphalt, except for the viscoelastic ratio. WO containing more asphaltenes and saturates or ash will promote the rapid aging of rejuvenated asphalt. Combined with chemical characteristics and molecular dynamics (MD) simulation, the interaction between WO and aged asphalt belongs to physical dissolution, and the rejuvenation process is achieved by restoring the colloid structure of asphalt and increasing molecular mobility. In the modification process, WO is mainly used to improve the intermediate fatigue resistance and low-temperature cracking resistance of asphalt in winter areas, and can also be used as an anti-aging agent, but will harm the high-temperature properties. The composite rejuvenation/modification of WO and crumb rubber (CR) makes the properties of asphalt more comprehensive. For asphalt mixture, the cracking resistance and the moisture susceptibility of WO recycled asphalt mixture are worse than hot mix asphalt (HMA). The future research focus is to evaluate the performance of WO recycled asphalt mixture and WO modified asphalt mixture after long-term aging and conduct field experiments combined with economic and environmental benefits analysis.